(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2020)
Return migration of internationally educated Chinese academics has been a significant feature of China’s higher education internationalization and a top government concern for boosting China’s development in the globalized knowledge economy. However, despite of the government’s expectation of returnee academics’ long-term settlement in China, there has been a trend of their re-migrating to settle overseas. It is necessary then to explore how their re-integration experiences in China affect their intention for future migration. This study employs a qualitative case study to explore the re-integration experiences for internationally educated Chinese academic returnees and their experiences are interpreted vis-à-vis the institutional and national contexts. The findings indicate that what appears to be personal struggles between cultures are actually reflective of competing powers of recognition of different cultural knowledges in the global internationalization of higher education.